2017
DOI: 10.1056/nejmoa1611179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive Blood-Pressure Treatment on Patient-Reported Outcomes

Abstract: BACKGROUND The previously published results of the Systolic Blood Pressure Intervention Trial showed that among participants with hypertension and an increased cardiovascular risk, but without diabetes, the rates of cardiovascular events were lower among those who were assigned to a target systolic blood pressure of less than 120 mm Hg (intensive treatment) than among those who were assigned to a target of less than 140 mm Hg (standard treatment). Whether such intensive treatment affected patient-reported outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 36 publications
0
137
0
Order By: Relevance
“…However, over the follow-up period, there were no statistically significant differences between groups in physical and mental health-related quality of life or depressive symptoms 2. This was unchanged in subgroup analyses, including age and number of coexisting conditions.…”
Section: Resultsmentioning
confidence: 79%
“…However, over the follow-up period, there were no statistically significant differences between groups in physical and mental health-related quality of life or depressive symptoms 2. This was unchanged in subgroup analyses, including age and number of coexisting conditions.…”
Section: Resultsmentioning
confidence: 79%
“…These results add to the literature demonstrating that lower blood pressure targets can be safe and are unassociated with declines in patient‐reported outcomes. In both SPRINT and the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial, intensive therapy was not associated with meaningful changes in health‐related quality of life . As with other clinical trials, the lower blood pressure target in SPRINT was unaccompanied by increases in injurious falls …”
Section: Discussionmentioning
confidence: 95%
“…A detailed analysis revealed that this was actually not the case, even in patients older than 75 years. In back-to-back papers published this year, Bress et al [10] and Berlowitz et al [11] looked at comparing costeffectiveness and willingness to pay, along with the quality of life for patients on intensive blood pressure-lowering therapy, respectively. The average age of the patients was 75 years of age in the patient satisfaction study, with data taken from the Veterans RAND 12-Item Health Survey [11] .…”
Section: Hypertension -Aj (Ton) Rabelink (The Netherlands)mentioning
confidence: 99%
“…In back-to-back papers published this year, Bress et al [10] and Berlowitz et al [11] looked at comparing costeffectiveness and willingness to pay, along with the quality of life for patients on intensive blood pressure-lowering therapy, respectively. The average age of the patients was 75 years of age in the patient satisfaction study, with data taken from the Veterans RAND 12-Item Health Survey [11] . Even with some side effects, such as increased dizziness, there was virtually no difference in quality of life scores for those in standard treatment versus patients in intensive treatment over a period of 48 months.…”
Section: Hypertension -Aj (Ton) Rabelink (The Netherlands)mentioning
confidence: 99%